Advertising agency compensation, client evaluation and switching costs: an extension of agency theory - Davies, Mark; Prince, Melvin (Journal of Current Issues and Research in Advertising, 2010)
We develop a theory of advertising agency compensation, client evaluation and switching costs, with extensions to agency theory. When clients are exposed to high switching costs, they become more vulnerable to the risk of agency costs. In response, clients can select compensation and evaluation decisions that convey fairness, signal their commitment, and invite agency reciprocity. With high switching costs, outcome-based compensation and formal evaluation procedures are likely. High switching costs are associated with signifi'cant relationship investments, mature relationships, large clients, formal evaluation, and with clients that use their agencies as strategic partners. Clients surveyed in North America support the theory. © 2010 Taylor and Francis Group, LLC.
Keywords: dept.mkt

A study of marketing standardization and performance of australian, japanese, and U.S. firms - Kustin, Richard Alan (Journal of Asia-pacific Business, 2010)
Given the continued importance of the globalization era, there is an ever-increasing interest in the correlation between marketing mix standardization and the firm's market performance. This issue focuses on the firm's pursuit of global markets in an environment conditional to internal and external market factors. The research examines factors on multinational firm's marketing mix (program and process marketing) from Australia, Japan, and the United States and the impact on market performance. The results are mixed providing some support for marketing standardization and profit performance. © Taylor & Francis Group, LLC.
Keywords: Australia; Global Marketing; Japan; Marketing Mix; Profit Performance; Standardization; Strategic Marketing; United States; corporate strategy; dept.mkt; globalization; marketing; multinational enterprise; standardization

Performance and standardization of Australian, Japanese and US firms - Kustin, Richard Alan (Asia Pacific Journal of Marketing and Logistics, 2010)
Purpose – Globalization has fostered greater interest in all aspects of standardization theory including the 4Ps of the marketing mix or program and process marketing. The purpose of this paper is to probe the question: “Is there a benefit to the firm's strategy of marketing standardization that correlates positively to the firm's profit?”. Design/methodology/approach – Multinational firms from Australia, Japan and the USA operating in a global environment were studied in order to correlate marketing standardization to profit performance. Several methods of analysis were used including regression and analysis of variance measures. Findings – The results indicate there is increasing support for a strategy of standardizing marketing mix components and contributing to a firm's profit performance. Originality/value – The paper adds to the current literature by providing further empirical research correlating marketing mix standardization to profit. © 2010, Emerald Group Publishing Limited
Keywords: Australia; Globalization; Japan; Marketing strategy; Standardization; United States of America; dept.mkt

The earth is flat, almost: measuring marketing standardization and profit performance of japanese and U.S. firms - Kustin, Richard Alan (Journal of Global Marketing, 2010)
Globalization has fostered greater interest in all aspects of standardization theory, including the four Ps (product, price, place [distribution], and promotion) of the marketing mix. The study researches the firm's strategy of marketing standardization as it correlates to the firm's profit. Multinational firms from Japan and the United States operating in a global environment were studied in order to correlate marketing standardization to profit performance. The results indicate there is increasing support for a strategy of standardizing marketing mix components and contributing to a firm's profit performance. © Taylor & Francis Group, LLC.
Keywords: Global marketing; Global strategy; Globalization; Marketing standardization; Profit performance; dept.mkt